Trichothiazole A, a dichlorinated polyketide containing an embedded thiazole isolated from Trichodesmium blooms. Issue 43 (25th October 2017) - Belisle, Richard S.; Via, Christopher W.; Schock, Tracey B.; Villareal, Tracy A.; Zimba, Paul V.; Beauchesne, Kevin R.; Moeller, Peter D.R.; Bertin, Matthew J.
Graphical abstract: Highlights: We have isolated and characterized the new natural product trichothiazole. Trichothiazole was moderately cytotoxic to Neuro-2A cells. Trichothiazole was isolated by environmental sampling of a cyanobacteria bloom. Abstract: Mass spectrometry-guided isolation of the lipophilic extract of Trichodesmium bloom material led to the isolation and structure characterization of a new thiazole-containing di-chlorinated polyketide (1 ). The structure of1 was deduced using 1D and 2D NMR analysis, high-resolution mass spectrometry analysis and complementary spectroscopic procedures. Trichothiazole A possesses interesting structural features, such as a terminal alkyne, two vinyl chlorides and a 2, 4-disubstituted thiazole. Trichothiazole A showed moderate cytotoxicity to Neuro-2 A cells (EC50 : 13.3 ± 1.1 μM).